To assess hemodynamic disturbances to the ostia of the renal arteries generated by the implantation of EVAR with a suprarenal fixation. Issue 18 (May 2020) - Salomon du Mont, Lucie; Parmentier, Anne-Laure; Puyraveau, Marc; Mauny, Frédéric; Guillon, Benoit; Rinckenbach, Simon; Costa, Patricia
Abstract: Introduction: The treatment of abdominal aortic aneurysm (AAA) is increasingly performed via endovascular aneurysm repair (EVAR). Different types of fixation are possible with EVAR, i.e., below (infrarenal fixation) or above (suprarenal fixation) the renal arteries. Hemodynamic alterations in renal arterial flow with suprarenal (SR) fixation remain to be demonstrated. The IFIXEAR (Impact of Supra-renal Fixation of EVAR on Hemodynamics of Renal Arteries) study is designed to assess the hemodynamic effects at the ostia of at least 1 renal artery, generated immediately post-surgery by the implantation of an aortic stent with SR fixation. Methods: IFIXEAR is a prospective, 2 center study. Every patient undergoing elective EVAR with SR fixation is eligible for inclusion. Patients with previous hemodynamic disturbances to the ostia of 1 of the renal arteries are not eligible. All patients undergo echocardiography and renal arteries duplex ultrasound within a month before surgery, and at 1 and 12 months after surgery. The primary endpoint is hemodynamic disturbance, defined as a peak systolic velocity greater than 120 cm/second, at the ostia of 1 of the renal arteries in the immediate postoperative period. Ethics and dissemination: The study was approved by the Ethics Committee "Comité de Protection des Personnes Ouest V" under the number 18/019-2 on April 20, 2018. All patients provide written informed consent before inclusion. The University Hospital of Besancon is the trial sponsor. Results of the study will be submitted for publication in a peer-reviewed international medical journal. Registration: The trial is registered with ClinicalTrials.gov (Identifier: NCT03594786, principal investigator: Dr Patricia Costa, Registered on April 24, 2018).